Relational Coordination in Inclusive Education: A Critical Review and Theoretical Extension Toward Emotional Responsiveness in Indonesia - Sally Fedrini; Ardi Kho (ProBisnis : Jurnal Manajemen, 2025)
Inclusive education in Indonesia often remains symbolic due to fragmented collaboration and hierarchical school cultures. Relational Coordination Theory (RCT) focusing on shared goals, shared knowledge, mutual respect, and quality communication has proven effective in high interdependence sectors like healthcare but is seldom applied in educational contexts in developing countries. This critical literature review aims to synthesize the theoretical development and empirical findings of RCT across sectors and propose its adaptation to foster emotional responsiveness, a school's capacity to address students' emotional needs in Indonesian inclusive schools. The synthesis confirms RCT's strong potential as a theoretical and diagnostic framework for enhancing collaboration among teachers, therapists, and support staff. The study further proposes a theoretical model linking structural inputs and relational coordination mechanisms to emotional responsiveness as a core outcome. Policy and practical implications for stakeholders are discussed, along with recommendations for future empirical research to test the model in the Indonesian context.